Investigating the Colonial Project of Domestic and Intragroup Violence in the Queer Indigenous Community - Aaliyah A. Gonzalez (Journal of Global Indigeneity)
Within Indigenous communities, there is often a lack of discussion of the ongoing harmful effects of the practice of colonial gender, sex, and sexuality. Within my paper are three poems I wrote tying together my personal relationships with the politics of settler colonialism. These poems intend to illustrate this violence within Indigenous Queer relationships as a colonial legacy that is sustained by homophobia, heterosexism, transphobia, and misogyny. In my first poem, titled “A Letter to My Brother,” I draw on settler scholar Sam McKegney’s (2011) concept that there are three harmful stereotypes available to Indigenous men: bloodthirsty savage, noble warrior, and drunken absentee (p. 258). The un/intentional undertaking of these colonial masculinities by Indigenous men perpetuates misogynistic settler colonial violence. In “Do Better for Our Daughters”, I draw on Diné scholar Jennifer Nez Denetdale’s idea that ‘tradition’ informed by hegemonic understandings of gender, sex, and sexuality perpetuates settler colonial violence against Indigenous peoples who do not abide by settler gender norms (2006; 2009). “Do Better for Our Daughters” displays this through the exploration of myself and other Indigenous Queer women’s marginalised experience of discrimination, devaluation and abuse in our relationships. In “Dating as a Native Girl”, I draw on Cree scholar Robyn Bourgeois’ (2018) discernment that the ongoing patriarchal gendered racist violence against Indigenous women has historical roots. This collection of poems illustrates that in our nonconsensual relationship with settler colonialism, imposed notions of gender, sex, and sexuality actively perpetuate the physical, mental, and spiritual violence against all Indigenous peoples because it constructs interpersonal relationships as sites to carry out settler colonial violence.